An Analysis Speech Act of Apology Strategy Reflected in Little Women Movie Directed by Greta Gerwig - Reza Ayu Amalia; Mujazin (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Communication is an important aspect for humans to interact with each other. In communicating, humans do not escape mistakes, be it in the form of speech or in action. Therefore, humans need an apology strategy to correct the mistakes they have made in speech or actions. The purpose of this study is to examine the types of apology strategies and also the apology factors used by the characters in the film Little Women directed by Greta Gerwig. This research is a qualitative descriptive study. The data in this study are the apologies uttered by the characters in the Little Women film directed by Greta Gerwig. The source of the data in this study was taken from the film Little Women directed by Greta Gerwig and also the transcript of the film. Data was collected by downloading the film and film transcript, then the researcher examined it using Trosborg's theory to examine apology strategies and Fraser's theory to examine apology factors. The researcher found 5 types and 11 sub types of apology strategies according to Trosborg's theory used in conversation. in the film â€œLittle Womenâ€ directed by Greta Gerwig. There are 5 types of apology factors, including the nature of the infraction, the severity of the infraction, the situation in which the infraction occurred, the relative familiarity between the interactants, the sex of the interactants. The researcher also found 8 types of apologies and 21 different sub-types of apology strategies according to Trosborg's theory.